Carotenoids modulate the hallmarks of cancer cells. (October 2015) - Niranjana, R; Gayathri, R; Nimish Mol, Stephen; Sugawara, T; Hirata, T; Miyashita, K; Ganesan, P
Highlights: Carotenoids modulate the hallmarks of cancer cells through multiple molecular mechanisms An increase in the circulating level of carotenoids reduced the risk of cancers Marine carotenoids possess comparatively potent anti-cancer effects over terrestrial carotenoids Abstract: Biologically active compounds are considered as powerful food factors that elicit profound effects on the maintenance of human health, and disease prevention. The research into how bioactive compounds work and their role in disease prevention in vitro and in vivo is rapidly expanding. Carotenoids are one among several classes of biologically active compounds that have been reported to possess greater antioxidant and anti-cancer activity. Today, this emerging class of nutrients is the driving force in the nutritional supplement industry, and serves as a new frontier in cancer and cardiovascular research. Cancer is one of the leading causes of death worldwide. It is the second most common disease responsible for maximum mortality with about 8.2 million deaths, and the global cancer burden rises to 14.1 million new cases in 2012. This review mainly focused to summarize the anti-cancer therapeutic targets of carotenoids by highlighting the important hallmarks of cancer in terms of (i) cell cycle arrest, (ii) resistance to apoptosis, (iii) metastasis and (iv) angiogenesis alongside the relation of carotenoids in cancer epidemiology.